Pewarna Plak Gigi dari Pewarna Alami Buah Naga Merah, Sebuah Tinjauan Cakupan - Wesilintang, Alit; Amaliya, Amaliya; Cahya Prasetyo , Budhi (Jurnal Kedokteran Gigi Terpadu, 2024)
Dental plaque identification uses disclosing agents to provide a better visual identification of dental plaque before the plaque control procedure. Studies show the use of natural ingredients for staining dental plaque, one of which is that red dragon fruit can be an effective alternative for evaluating dental plaque control. This scoping review aims to examine further natural dental plaque coloring from red dragon fruit. This literature review uses a scoping review study design that refers to the PRISMA-ScR analysis and uses the PCC framework. Article searches were carried out using key word (red pitaya) AND (disclosing agent), AND (dental plaque) in 5 online databases, namely PubMed, Science Direct, Wiley, SAGE, and Google Scholar. The selection of articles was carried out based on inclusion and exclusion criteria. Initial search obtained 170 articles, then selected according to inclusion and exclusion criteria resulting 9 articles. The results show dental plaque colorant from red dragon fruit extract can effectively color dental plaque as well as disclosing agents. Red dragon fruit extract meets the requirements for being a dental plaque coloring agent. At a concentration of 75%, red dragon fruit extract can color dental plaque well and produces optimal coloring at a concentration of 100%.